Socio-Ecological Review of Former Mine Tourism: Case Study in SETIGI Tourism Area - Deny Wahyu Apriadi; Toetik Koesbardiati (Jurnal Ilmu Sosial dan Humaniora, 2025)
SETIGI represents land that has lost its productivity and natural vegetation because it has been turned into a limestone mine. This condition has turned SETIGI into critical, barren land and a dumping ground for waste. Now, SETIGI has transformed into community-based tourism through the initiative of the local community, which has participatively and sustainably rehabilitated the land as a tourist site and carried out environmental restoration activities such as reforestation, with the aim of restoring the ecological function of the land. This study was conducted to analyse the socio-ecological aspects of post-mining tourism, both in terms of community behaviour and ecological factors related to tourism activities. This research uses qualitative methods with in-depth interviews with 8 informants, literature reviews, and description of results with triangulation validity. The results of this study indicate that community behaviour is related to environmental conditions. The establishment of SETIGI community-based tourism with the SES framework has brought about significant changes in the environment through sustainable land rehabilitation by local communities. Simple planning and activities without management are now systematic and organised. From a socio-cultural perspective, the community is more aware of the importance of cooperation and solidarity. From an ecological, there is greater concern for environmental cleanliness and active participation in its preservation. The socio-ecological impact of SETIGI's development also aims to improve the quality of human resources, emphasising that this change is not only about physical land, but also holistic and sustainable socio-ecological transformation thanks to the central role of local communities in accordance with the SES framework.